Projek Perubahan (Change Project) Tentang Pendidikan yang berpihak pada peserta didik dan Memerdekakan peserta Didik DALAM Pendidikan Abad 21 - Agnes Monika Siregar; Liesna Andriany (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Indonesian education is experiencing changes and developments through curriculum reform strategies in line with current developments. Strengthening character with Pancasila values is emphasized in Merdeka Belajar, a government breakthrough to develop the unique potential of each student. The purpose of this research is to carry out an in-depth study of the implementation of the Pancasila Student Profile Program given to students. How the Pancasila Student Profile Program is implemented in schools, and whether the program meets the criteria for supporting students. The method in this research is a qualitative method. The data collection technique used is documentation, which involves collecting library document sources. The results of the literature study show the success of many schools in implementing Pancasila student profile learning techniques, with activities inside and outside the classroom to strengthen students' character according to national education goals. Apart from that, the factors inhibiting the implementation of this project involve low awareness and understanding of Pancasila values, the existence of conflicting values, as well as factors from educators such as minimal study time, limited lesson substance, and low interest from students